A study to determine scar integrity in pregnant women with previous lower segment caesarean section - Mangla, Divya; Singh, Sunder Pal; ., Swasty; Chauhan, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The purpose of this study was to assess the radiological characteristics of previous caesarean section scar and their correlation with clinico-pathological parameters, in order to decide mode of delivery. Methods: This prospective longitudinal study was conducted on 200 women who had previous caesarean section and were at 36 weeks or more of gestation period and came in labor or taken for caesarean section from the antenatal clinic of Department of Obstetrics & Gynecology, Subharti Medical College from the period January 2011 to December 2013.Radiological evaluation of previous caesarean section scar was done using transvaginal sonography (TVS) for all the women 54 women went through caesarean section and for them peroperatively mechanical measurement of scar thickness was done by ophthalmic calliper to correlate with the scar thickness in USG. Peroperatively scar tissue was taken for histopathological evaluation. Results: 168 women with previous caesarean section underwent trial of labor and 114 women had vaginal delivery (67.8%). As per this study there was a statistically significant correlation between scar thickness measured at or after 36 weeks of gestation and mode of delivery (p<.0001). Statistically significant correlation was also found between scar thickness measured prior to shifting for caesarean and peroperative scar thickness measurement by calliper. In histopathology, presence of fibro-collagenous tissue indicates weaker scar. Conclusions: TVS should be used as an effective tool to measure the scar integrity, which will be helpful in deciding the mode of delivery. This will improve predictability of scar dehiscence or scar rupture in labor and hence choice of patients for successful VBAC may be made with greater accuracy. The pathological and biomechanical behavior evaluation of scar was done in this study in order to strengthen the radiological finding to decide the mode of delivery.